The Effect of Hydro-alcoholic Extract of Saffron Stigma ( Crocus satious L.) on Metabolic Control Parameters, Liver Enzymes, and Renal Function Parameters in Type 2 Diabetic Patients - AR Milajerdi; AGh Djazayeri; Sh Jazayeri; N Hashemzadeh; E Shirzadi; Zh Derakhshan; Sh Akhondzadeh (Institue of Medicinal Plants, ACECR, 2016)
Background: Uncontrolled metabolic status of diabetes induces multiple complications, such as liver and renal dysfunctions. Saffron as an herbal medicine may improve diabetes metabolic control. Objective: The aim of this study was to investigate the effect of hydro-alcoholic extract of saffron on metabolic control parameters, liver enzymes, and renal function parameters in type 2 diabetic patients. Methods: In this triple-blind clinical trial, 54 type 2 diabetic patients randomly consumed 15 mg saffron or placebo capsules twice a day for 8 weeks. The following measurements were made during the study: 1. Fasting and 2-hour blood glucose, glycosylated hemoglobin, cholesterol, triglyceride, low and high density lipoproteins, alkaline phosphatase, aspartate and alanine amino transferase, uric acid, blood urea nitrogen, and creatinine; 2. Physical activity at the beginning and the end of the study; 3. dietary intakes at the beginning, midst, and end of the study; 4. anthropometric parameters every 2 weeks; 5. blood pressure every 2 weeks. The data were analyzed using the SPSS.18 software. Results: Fasting and 2-hour blood glucose, triglyceride, uric acid, and blood urea nitrogen decreased (35.5, 38.5, 0.62, and 4.5 mg/dl, respectively), and high density lipoprotein increased, significantly in the saffron group (P<0.05). Changes in lipid profile components other than triglycerides were not statistically significant in the two groups. Significant changes in blood pressure, dietary intakes, and physical activity were not seen in either group either (P>0.05). Conclusion: Saffron hydro-alcoholic extract may improve type 2 diabetic patients' condition through helping control blood glucose and some of the lipid profiles components. It can also improve renal function, which may be related to its antioxidant properties.